The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1088/0957-0233/10/3/018
|View full text |Cite
|
Sign up to set email alerts
|

A frequency-modulated continuous wave birefringent fibre-optic strain sensor based on a Sagnac ring configuration

Abstract: Two-mode fibre interferometers have been shown to be well suited as optical fibre strain sensors because (i) they have a higher resolution than do intensity modulation-based strain sensors and (ii) they have a simple geometry since the reference and signal light beams propagate along a single fibre core. This paper discusses a Sagnac ring configuration of polarization-maintaining fibre strain sensor based on frequency-modulation continuous wave technology wherein the basic sensor layout consists of a frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…Polarization-maintaining fiber (PMF) is usually used in Sagnac interferometers to introduce optical path difference and cause interference between the two counterpropagating waves in the fiber loop [3][4][5][6][7]. However, conventional PMFs (e.g., Panda and bow-tie PMFs) have a high thermal sensitivity due to the large thermal expansion coefficient difference between boron-doped stress-applying parts and the cladding (normally pure silica).…”
Section: Introductionmentioning
confidence: 99%
“…Polarization-maintaining fiber (PMF) is usually used in Sagnac interferometers to introduce optical path difference and cause interference between the two counterpropagating waves in the fiber loop [3][4][5][6][7]. However, conventional PMFs (e.g., Panda and bow-tie PMFs) have a high thermal sensitivity due to the large thermal expansion coefficient difference between boron-doped stress-applying parts and the cladding (normally pure silica).…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, the same authors reported similar work using a frequency-modulated continuous wave (Campbell et al, 1999).…”
Section: Yearmentioning
confidence: 89%
“…Breakthrough of Hi-Bi FLM configurations 1997 Temperature sensor ; temperature sensing in NIR ; strain sensor (Campbell et al, 1997(Campbell et al, ) 1999 Strain sensor (Campbell et al, 1999) 2004 Temperature PCF sensor (Kim, D. H. & Kang, 2004); temperature insensitivity using PCF (Zhao et al, 2004(Zhao et al, ) 2005 Interrogation system using PCF (Yang et al, 2005); displacement sensor (Liu et al, 2005) 2006 Liquid level sensor (Dong, B. et al, 2006); FBG interrogation system ; LPG/Hi-Bi FLM (Frazao et al, 2006b) 2007 Review of Hi-Bi FLM sensors (Frazao et al, 2007a); strain PCF sensor (Dong, X. Y. et al, 2007;Frazao et al, 2007b) ; chemical etching (Frazao et al, 2007c); concatenated FLM (Frazao et al, 2007d) 2008 Temperature Erbium Hi-Bi fiber (Frazao et al, 2008a); refractive index sensor (Frazao et al, 2008b); multiparameter sensor using side-hole fiber (Frazao et al, 2008c); pressure PCF sensor (Fu et al, 2008); FBG/Hi-Bi FLM (Zhou et al, 2008); current sensor (Marques et al, 2008) 2009 Multiplexing Hi-Bi FLM (Fu et al, 2009); strain and temperature discrimination using two Hi-Bi fibers ); hollow-core PCF sensor (Kim, G. et al, 2009); holey fiber filled with metal indium (Kim, B. H. et al, 2009) 2010 Torsion PCF sensor ; curvature PCF sensor (Gong et al, 2010); pressure-induced SMF ; long distance remote interrogation system (Lee et al, 2010); small core PCF (Andre et al, 2010); intensity strain sensor (Qian et al, 2010); suspended twin-core ; displacement PCF sensor 2011 Hi-Bi FLM with an output port probe ; LPG/Sagnac Loop (Kang et al, 2011); curvature PCF sensor (Hwang et al, 2011); Hi-Bi photonic bandgap Bragg fiber …”
Section: Yearmentioning
confidence: 99%
“…FLMs made of highly birefringent fiber (HiBi-FLM) have several advantages, including input polarization independence and high extinction ratio. Besides the gyroscope application, various kinds of sensors based on FLMs have been realized [3], such as temperature sensors [2,4], strain sensors [5,6], pressure sensors, liquid level sensors [7], biochemical sensors, UV detection [8] and multiparameter measurement [9][10][11].…”
Section: Introductionmentioning
confidence: 99%